Methods for Continuous Non-invasive Measurement of Blood Pressure: Pulse Transit Time a Review - Kaur, Harleen (Asian Journal of Pharmaceutics (AJP), 2018)
Blood pressure (BP) measurement is regarded as one of the most important parameters in the clinical evaluation of patients. It is helpful in both acute and chronic cases. Most medical examinations include BP measurement as it is the best indicator of cardiovascular health. In some cases, it is very important to examine the status of pressure valves continuously for long time periods. To prevent premature death, it can be used for daily health-care monitoring. The main problem with BP measurement is that all existing techniques use an inflatable cuff which is a discrete technique and may cause discomfort for the patients. Recently, few alternative techniques have been developed for non-invasive continuous measurement of BP. This review focuses on brief discussion of some of the methods for BP measurement both invasive and non-invasive and due to fewer side-effects and convenience of attachment of sensors of photoplethysmogram (PPG), this review mainly focuses on the plethysmography technique using pulse transit time for BP measurement. At present, many researchers are working on this method, and it has the potential to be the most widely used technique for a long time non-invasive continuous observation of BP in the future. This review also briefly discussed some of the artifact removal techniques in the PPG waveform and inaccuracies related to sensors due to the external factors such as noise and temperature.